2020
DOI: 10.1111/aor.13628
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support during and after bilateral sequential lung transplantation in patients with pulmonary artery hypertension

Abstract: The use of extracorporeal membrane oxygenator instead of standard cardiopulmonary bypass during lung transplantation is debatable. Moreover, recently, the concept of prolonged postoperative extracorporeal membrane oxygenator (ECMO) support has been introduced in many transplant centers to prevent primary graft dysfunction (PGD) and improve early and long-term results.The objective of this study was to review the results of our extracorporeal life support strategy during and after bilateral sequential lung tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…It might probably due to excessive bleeding and transfusion requirements and prolonged ischemic time during transplantation. Finally, other groups have recently reported on the use of ECMO support profilactically in lung transplantation showed an improve survival, which could demonstrate the benefit of prophylactic ECMO [25,26]. However, in our center ECMO was usually only reserved for complex transplantation or to support intraoperative unstable patients, which may also influence the outcome.…”
Section: Discussionmentioning
confidence: 58%
“…It might probably due to excessive bleeding and transfusion requirements and prolonged ischemic time during transplantation. Finally, other groups have recently reported on the use of ECMO support profilactically in lung transplantation showed an improve survival, which could demonstrate the benefit of prophylactic ECMO [25,26]. However, in our center ECMO was usually only reserved for complex transplantation or to support intraoperative unstable patients, which may also influence the outcome.…”
Section: Discussionmentioning
confidence: 58%
“…Indications for intra-operative ECMO include a combination of the following conditions[ 4 ]: (1) Hypercapnia; (2) Low arterial saturation (< 90%); (3) Low cardiac index (< 2 L/min/m 2 ); and (4) Significant increase in pulmonary pressure. Between 2017 and 2020, five studies reported detailed outcomes on the use of ECMO during LTx (Table 3 )[ 41 , 43 - 46 ] . Central (c) ECMO is commonly used in the intra-operative setting.…”
Section: Ecmo In the Intra-operative Settingmentioning
confidence: 99%
“…Dell'Amore et al [71] reported in 2020 their analysis of 38 patients who underwent LT and who had peripheral VA ECMO as a planned prolongation of ECMO into the postoperative period. They described lower incidence of PGD and improved survival in the postoperatively ECMO supported patients.…”
Section: "Planned" Continuation Of Intraoperative Ecmo Into Postoperative Periodmentioning
confidence: 99%
“…They described lower incidence of PGD and improved survival in the postoperatively ECMO supported patients. Table 6 lists case series of patients with planned postoperatively extended intraoperative ECMO [59,[68][69][70][71].…”
Section: "Planned" Continuation Of Intraoperative Ecmo Into Postoperative Periodmentioning
confidence: 99%